Madhyama Pratipad: Nepal’s Middle Path Ambition through Non-alignment - Bhattarai, Gaurav; Pulami, Manish Jung (Journal of Foreign Affairs, 2022)
The geopolitical variable alone is not sufficient to understand Nepal’s entry into NAM and its relevance. While very little literature has been produced on Nepal’s non-alignment, what exists is also limited to either speeches or statements delivered by Nepali leaders at the conferences Non-Aligned Movement (NAM). Still, while scanning the perspective of Non-Nepali Cold War foreign policy analysts in the literature produced on Himalayan geopolitics, it can be clearly observed that Nepal’s voyage to non-alignment was driven by the Indian response to the bipolarity in Cold War. Such a perspective, however, dismisses the influence that MadhyamaPratipad (the concept of the middle path) had in the evolution of Nepal’s foreign policy priorities as a unified state in 1769. MadhyamaPratipad, here, should be understood as the cultural and civilizational philosophy, which Nepal has accommodated in its world view for centuries. Hence, Nepal’s shift to non-alignment was not abrupt and impulsive. Rather it was triggered by the MadhyamaPratipad, which was also realized by the founder of modern Nepal, Prithivi Narayan Shah. While non-alignment and MadhyamaPratipad differ in their approaches, their objectives remain the same: balancing. While non-alignment demands balancing by not being aligned to any security bloc, MadhyamaPratipad appeals to balancing by treading a middle path. Thus, this qualitative study argues how the historical experience of balancing made it easier for the Himalayan state to adapt to the non-aligned policy and posture. Accordingly, non-alignment to Nepal is not only a survival strategy but also a historical expression of its cultural and civilizational philosophy. Therefore, any attempt to understand Nepal’s foreign policy of non-alignment only from the grand narratives of geopolitics and changing dynamics in the regional and international security environment would not be sufficient to weigh the rationale and relevance of non-alignment for Nepal. Today, India’s perceptible shift to multi-alignment and China’s emphasis on the Xi Jinping Thought have already raised the question of the relevance of non-alignment for Nepal. The answers lie in Nepal’s historical experience of balancing.